2016
DOI: 10.1556/2060.103.2016.3.1
|View full text |Cite|
|
Sign up to set email alerts
|

VESTPD as a measure of ventilatory acclimatization to hypobaric hypoxia

Abstract: This study compared the ventilation response to an incremental ergometer exercise at two altitudes: 633 mmHg (resident altitude = 1,600 m) and following acute decompression to 455 mmHg (≈4,350 m altitude) in eight male cyclists and runners. At 455 mmHg, the V E STPD at RER <1.0 was significantly lower and the V E BTPS was higher because of higher breathing frequency; at VO 2 max, both V E STPD and V E BTPS were not significantly different. As percent of VO 2 max, the V E BTPS was nearly identical and V E STPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…These data were obtained during a research study previously reported with a different focus (21)(22)(23). Eight male volunteers were cyclists and runners consistently performing an average of 6 hr/ wk of moderate and 2-3 hr/wk of vigorous exercise during the year prior to, and during the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were obtained during a research study previously reported with a different focus (21)(22)(23). Eight male volunteers were cyclists and runners consistently performing an average of 6 hr/ wk of moderate and 2-3 hr/wk of vigorous exercise during the year prior to, and during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Each 35-W work rate increment was divided into four quarters to coincide with the 15-s measurement intervals. The average number of recorded points for the 16 tests was 22 (range: [16][17][18][19][20][21][22][23][24][25][26]. The measured values for the tests at 633 and 455 mmHg were then superimposed and compared at identical work rates.…”
Section: Methodsmentioning
confidence: 99%